2022
DOI: 10.1186/s13047-022-00523-w
|View full text |Cite
|
Sign up to set email alerts
|

Opinions about the most appropriate surgical management of diabetes‐related foot infection: a cross‐sectional survey

Abstract: Background There is a lack of high quality evidence to guide the optimal management of diabetes-related foot infection, particularly in cases of severe diabetes-related foot infection and diabetes-related foot osteomyelitis. This study examined the opinions of surgeons about the preferred management of severe diabetes-related foot infection. Methods Vascular and orthopaedic surgeons in Australia and New Zealand were invited to complete an online su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A survey of Australian Infectious Diseases (ID) physicians reported that management of patients with DFI accounted for approximately 19% of ID physician caseload, and there was marked heterogeneity in antimicrobial treatment regimen recommendations (Commons et al 2018). A survey of Australian and New Zealand vascular and orthopaedic surgeons found they had relatively similar management practices, but few were guided by best practice clinical guidelines for DFI (Seng et al 2022). An Australian study reported microbiology results from patients with DFI managed in a tertiary inpatient setting and revealed antimicrobial stewardship opportunities with overuse of antipseudomonal agents despite adherence to national antibiotic prescribing guidelines (Hand et al 2019).…”
Section: Diabetes-related Foot Infections: Microbiology and Microbiomementioning
confidence: 99%
“…A survey of Australian Infectious Diseases (ID) physicians reported that management of patients with DFI accounted for approximately 19% of ID physician caseload, and there was marked heterogeneity in antimicrobial treatment regimen recommendations (Commons et al 2018). A survey of Australian and New Zealand vascular and orthopaedic surgeons found they had relatively similar management practices, but few were guided by best practice clinical guidelines for DFI (Seng et al 2022). An Australian study reported microbiology results from patients with DFI managed in a tertiary inpatient setting and revealed antimicrobial stewardship opportunities with overuse of antipseudomonal agents despite adherence to national antibiotic prescribing guidelines (Hand et al 2019).…”
Section: Diabetes-related Foot Infections: Microbiology and Microbiomementioning
confidence: 99%